2013
DOI: 10.3109/09638288.2013.791726
|View full text |Cite
|
Sign up to set email alerts
|

The roles, barriers and experiences of rehabilitation therapists in disaster relief: post-earthquake Haiti 2010

Abstract: Understanding the roles and experiences of therapists in disaster relief setting is important Certain barriers to providing care in post-disaster settings exist Those participating in disaster response should be well prepared and aware of that they might be asked to do.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 10 publications
1
19
0
Order By: Relevance
“…Prior to the January 2010 earthquake, rehabilitation services in Haiti were scarce [1][2][3][4]. For a population in which one in six households included a person with a disability [5], most of these services were provided through non-governmental organizations (NGOs) and religious institutions [1,6].…”
Section: Introductionmentioning
confidence: 99%
“…Prior to the January 2010 earthquake, rehabilitation services in Haiti were scarce [1][2][3][4]. For a population in which one in six households included a person with a disability [5], most of these services were provided through non-governmental organizations (NGOs) and religious institutions [1,6].…”
Section: Introductionmentioning
confidence: 99%
“…Additional articles relating to "difficulty" that: (i) reported on the negative experience of healthcare workers during medical humanitarian aid, including disaster relief activities; and (ii) discussed obstacles and hazards with respect to humanitarian aid, were included. This search yielded eight manuscripts (1 Japanese, 7 English) for item selection, of which 167 were excluded King et al, ; Sakamoto et al , ; Yang et al, ; Lopes Cardozo et al, ; Ripp et al, ; Hunt et al, ; Klappa et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…Such stressful circumstances disturb medical relief activities and cause psychological distress. Much of the previous literature has investigated an increased risk of mental health problems among disaster workers (Lopes Cardozo et al, ; Klappa et al, ; Sakuma et al, ). However, few studies have assessed the difficulties faced by healthcare workers attempting to provide medical care and perform activities of daily life in dispatched areas.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has identified experiences of medical personnel and health professionals working in conflict situations, and after hurricanes or earthquakes. A range of issues associated with responses were highlighted including motivation to respond, preparedness and role (Harrison, 2007;Klappa et al, 2010;Stangeland, 2010;Gowing et al 2017), challenges with coping, reintegration on homecoming (Rivers et al 2013;Kelly et al, 2014;Brooks et al 2015), and perceptions of personal and professional benefits gained (Scanell-Desch and Doherty, 2010;Richardson and Ardagh, 2013). However limited literature refers to short-term responses or the experiences of rehabilitation professionals.…”
Section: Introductionmentioning
confidence: 99%